Effect of finishing and polishing on surface roughness of composite resins after bleaching - Bruna Fortes Bittencourt; Giovana Mongruel Gomes; Felipe Auer Trentini; Mônica Regina de Azevedo; João Carlos Gomes; Osnara Maria Mongruel Gomes (Universidade Estadual de Campinas, 2009)
Aim: To evaluate the influence of finishing and polishing techniques on the surface roughness of two composite resins (CRs) subjected to bleaching procedure. Methods: Forty-eight CR specimens were divided into six groups (n=8). For G1 to G3, a microhybrid CR (Opallis; FGM) was used, and G4 to G6, received a nanohybrid CR (Brilliant NewLine; Coltène/Whaledent). All specimens were subjected to bleaching procedure with 35% hydrogen peroxide (two 45-min applications, with a 5-day interval). The surface roughness of all specimens was evaluated before and after the bleaching and/or finishing/polishing (Ra parameter) by a roughness meter. After bleaching, the groups were subjected to finishing and polishing procedures: G2 and G5 - felt discs + diamond pastes; and G3 and G6 - silicon rubber tips. The control groups (G1 and G4) had no finishing or polishing treatment after bleaching. Data were analyzed by ANOVA and Tukey's posttest, and t test for paired samples (α=0.05). Results: bleaching treatment increased Ra values for the nanohybrid CR specimens, but both finishing/polishing techniques were able to reduce these values; for the microhybrid specimens, only finishing/polishing with silicon rubber tips decreased the roughness values. Conclusions: For both microhybrid and nanohybrid CRs, the silicon rubber tips were effective to reduce the surface roughness after bleaching procedure.